The Effect of Economic Growth, Agricultural Land, and Trade Openness Moderated By Population Density on Deforestation in OIC Countries - Annisa Rahma Febriyanti; Ririn Tri Ratnasari; Akhmad Kusuma Wardhana (Quantitative Economics and Management Studies, 2022)
Deforestation is a serious environmental problem in the OIC countries. From 1990 to 2016 based on 2019 OIC Environment Report data, compared to other groups outside the OIC, the OIC deforestation rate reached >10% on average, which was much higher. The focus of this study examines the effect of economic growth, agricultural land, and trade openness moderated by population density on deforestation. This study uses a quantitative approach and a Moderated Regression Analysis technique with a sample of 15 OIC countries from 2010-2019 taken from the purposive sampling method. The test results clarify that economic growth and agricultural land have a significant effect on the rate of deforestation, while the effect of trade openness is not significant on the rate of deforestation. From the results of the moderating variable, only agricultural land which has a significant effect on deforestation is moderated by population density. These results confirm Kuznets' environmental theory and environmental externality theory, and can be used as material for the government's evaluation to reduce deforestation rates and maintain forest sustainability according to SDG's No.15 agenda by considering demographic aspects such as population density. This study is limited to the 15 OIC countries that are the research sample due to their high forest fluctuations. s evaluation to reduce deforestation rates and maintain forest sustainability according to SDG's No.15 agenda by considering demographic aspects such as population density. This study is limited to the 15 OIC countries that are the research sample due to their high forest fluctuations. s evaluation to reduce deforestation rates and maintain forest sustainability according to SDG's No.15 agenda by considering demographic aspects such as population density. This study is limited to the 15 OIC countries that are the research sample due to their high forest fluctuations.